A sustainable route from corn stalks to N, P-dual doping carbon sheets toward high performance sodium-ion batteries anode. (April 2018) - Qin, Decai; Liu, Zhanying; Zhao, Yanzhang; Xu, Guiyin; Zhang, Fang; Zhang, Xiaogang
Abstract: High performance is indispensable for amorphous carbon materials toward sodium-ion batteries anode. Heteroatom doping has proved to be an effective strategy to improve the electrochemical performance of carbon-based materials. In this paper, N, P dual-doped carbon sheets (N, PCS) from the rinds of corn stalks have been successfully synthesized via a hydrothermal reaction using the cheap (NH4 )2 HPO4 as nitrogen and phosphorus source. SEM and TEM images showed that the N, PCS was composed of loose and stacked graphitic carbon sheets, which facilitated the penetration of electrolyte and ion diffusion. Higher I D / I G value (1.692) implied more defective sites on the surface of graphitic sheet to be generated after N and P co-doping, which combined with larger graphene layer distance (0.391 nm) contributed to the high performance of the N, PCS. When used as anode for sodium ion batteries, it presents a specific capacity of 277 mAh g −1 after 100 cycles at 0.25C, and a specific capacity of 202 mAh g −1 after 200 cycles at 1C. Even at a high rate of 5C, a stable specific capacity of 105 mAh g −1 still could be delivered after 2000 cycles, suggesting an excellent cycle stability and superior rate capability. Graphical abstract: Image 1